2016
DOI: 10.1038/mi.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Host innate inflammatory factors and staphylococcal protein A influence the duration of human Staphylococcus aureus nasal carriage

Abstract: Human Staphylococcus aureus (SA) nasal carriage provides a reservoir for the dissemination of infectious strains; however, factors regulating the establishment and persistence of nasal colonization are mostly unknown. We measured carriage duration and nasal fluid inflammatory markers after nasally inoculating healthy participants with their previously isolated SA strains. Ten out of 15 studies resulted in rapid clearance (9±6 days) that corresponded with upregulated chemokines, growth factors, and predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 50 publications
9
46
1
2
Order By: Relevance
“…A decreased inflammatory response to a carried strain presumably results in reduced clearance of that strain and may lead to longer carriage. These results are consistent with a recent study by Cole et al that observed an increased inflammatory response during nasal S. aureus clearance but not carriage (9), as well as a study by Nouwen et al (10) that reported that persistent carriers who were artificially inoculated with a mixture of S. aureus strains selected for their own strain and noncarriers artificially inoculated with S. aureus immediately purged the strain.…”
Section: Discussionsupporting
confidence: 92%
“…A decreased inflammatory response to a carried strain presumably results in reduced clearance of that strain and may lead to longer carriage. These results are consistent with a recent study by Cole et al that observed an increased inflammatory response during nasal S. aureus clearance but not carriage (9), as well as a study by Nouwen et al (10) that reported that persistent carriers who were artificially inoculated with a mixture of S. aureus strains selected for their own strain and noncarriers artificially inoculated with S. aureus immediately purged the strain.…”
Section: Discussionsupporting
confidence: 92%
“…Nasal fluids were collected at days 3, 8, 11, 15 or 16, 23 or 24, and 31 or 32 postinoculation. We previously reported that in healthy nonsmokers, 10 of 15 studies resulted in the clearance of inoculated S. aureus within 1 month (18). For active smokers, only 6 of the 19 studies resulted in clearance of nasal S. aureus within the month, and the average Ϯ standard deviation (SD) carriage duration was at minimum 30 Ϯ 2 days, as follow-up did not extend beyond 34 days (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…One week after the last application, S. aureus clearance was confirmed and nasal fluids were collected for baseline measurements of mucosal immune status. A week later, nasal swabs were again collected in order to confirm the absence of nasal S. aureus and the restoration of resident non-S. aureus nasal flora to premupirocin levels (18). Each participant then self-applied his or her previously isolated S. aureus strain to each nostril (participant and S. aureus isolate data are shown in Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, targetrons have also enabled the first directly targeted chromosomal mutations in the intracellular bacterial pathogen Chlamydia trachomatis (Johnson and Fisher 2013). Targetrons continue to be used in diverse bacteria for analysis of pathogenicity determinants (Buchan et al 2009;Cole et al 2016;Herrera et al 2016;Kint et al 2017), identification of new antibiotic targets (Zoraghi et al 2011;Donnelly et al 2017), construction of attenuated vaccine strains (Harper et al 2016), and the engineering of industrially important bacteria for increased biofuel and chemical production (Hong et al 2014;Dai et al 2016;Xue et al 2016).…”
Section: Biological Insights and Conclusion Frommentioning
confidence: 99%